(3GdEYdGe GdYQHj(B- (3GdChQhHj (B:s (3MhGQ ef CLd GdeSJbHd (B/s - (3TMGOI, egOjs; (3LhGOs ((3HjQhJ (B-(3dHfGf (B:s (3OGQ HdGd ,s, 1998)
(3MJi SfhGJ bdjdI eGVjI cGfJ cdeI GdYhdI eLQO JYHjQ GcGOjej dG jTYQ GdcKjQhf HhLhO Mhdge h Pdc bHd Gf jJMhd Gdi hGbY edehS VGZW jJjM aQUG h jaQV eNGWQ NGUI aj eLGdjf QFjSSjf geG GdGbJUGO h GdEYdGe GddPjf GUHMG YGdejjf HGdcGed aGdJhLgGJ h GdeTcdGJ GdEbJUGOjI JfJbd ef Gbdje Gdi GNQ HSQYI cHjQI h cd TYhH GdYGde JJGHY GdMOK GdhGMO aj faS GdhbJ JbQjHG h gh eG jaQV Ydi cGaI GbGdje GdYGde Gf JJMGhQ HehVhYjI hhVhM Mhd gPg GdbVGjG h NGUI eSGdI GdGYdGe aGdGYdGe de jYO efP hbJ Whjd eLQO bVjI KbGajI h de jYO cPdc eSGdI afjI (B-(3JcfhdhLjI QZe GgejI Pdc h GfeG GUHM bVjI SjGSI YGeI JWQM eTcdGJ ddJYGed eYgG cGdaVGA GdGYdGej GdeaJhM h UhQI cd WQa dOi GdWQa GdGNQ h eTcdGJ GdJYUH h GdJWQa h GdYdGbI Hjf GdMVGQGJ h GdVhGHW GdbGfhfjI dMQjI GdJYHjQ h GdMOhO GdJj JaQVgG GdfXe GdGLJeGYjI aj ehGLgI GdGYdGe h gj cdgG h ZjQgG bVGjG JbY aj HDQI GgJeGe GdeDJeQ GdPj ffTQ aj gPG GdcJGH GYeGdg GdcGedI h GdPj fXeg eQcR GdOQGSGJ GdYQHj GdGhQhHj HOGjI GdYGe (B1998 (3aj GdHMQjf Mhd GdGYdGe GdYQHj GdGhQhHj MhGQ ef GLd GdeSJbHd(B.s
Keywords: (3GdEYdGe GdYQHjs; (3GdEYdGe GdYQHj GdChQhHjs